Moderate-intensity stepping in older adults: insights from treadmill walking and daily living - T. Yates; J Henson; P. McBride; B Maylor; L. Y. Herring; J. A. Sargeant; M. J. Davies; P. C. Dempsey; A. V. Rowlands; C. L. Edwardson (BMC, 2023)
Abstract Background A step cadence of 100 steps/minute is widely used to define moderate-intensity walking. However, the generalizability of this threshold to different populations needs further research. We investigate moderate-intensity step cadence values during treadmill walking and daily living in older adults. Methods Older adults (≥ 60 years) were recruited from urban community venues. Data collection included 7 days of physical activity measured by an activPAL3™ thigh worn device, followed by a laboratory visit involving a 60-min assessment of resting metabolic rate, then a treadmill assessment with expired gas measured using a breath-by-breath analyser and steps measured by an activPAL3™. Treadmill stages were undertaken in a random order and lasted 5 min each at speeds of 1, 2, 3, 4 and 5 km/h. Metabolic equivalent values were determined for each stage as standardised values (METSstandard) and as multiples of resting metabolic rate (METSrelative). A value of 3 METSstandard defined moderate-intensity stepping. Segmented generalised estimating equations modelled the association between step cadence and MET values. Results The study included 53 participants (median age = 75, years, BMI = 28.0 kg/m2, 45.3% women). At 2 km/h, the median METSstandard and METSrelative values were above 3 with a median cadence of 81.00 (IQR 72.00, 88.67) steps/minute. The predicted cadence at 3 METSstandard was 70.3 (95% CI 61.4, 75.8) steps/minute. During free-living, participants undertook median (IQR) of 6988 (5933, 9211) steps/day, of which 2554 (1297, 4456) steps/day were undertaken in continuous stepping bouts lasting ≥ 1 min. For bouted daily steps, 96.4% (90.7%, 98.9%) were undertaken at ≥ 70 steps/minute. Conclusion A threshold as low as 70 steps/minute may be reflective of moderate-intensity stepping in older adults, with the vast majority of all bouted free-living stepping occurring above this threshold.